Heavy Metals Residues in Bivalve Mollusks in Fayoum Province and their Potential Health Hazards - Abdelhalim , Marwa A.M.; Abdelrahman, Hosny A.; Hamed , Eslam E. (Journal of Advanced Veterinary Research, 2023)
Bivalves Mollusks have a potential benefit which include protection from anemia due to its content of iron and vit B12 in addition they pose a threat in promoting the ability to be contaminated by different heavy metals residues as a result of mining, industrial production untreated sewage sludge. Hg, Pb, Cd, As and Cr are the main five toxic heavy metals that induce human poisoning. For evaluation of Hg, Pb, Cd, As and Cr residues in Bivalve Mollusks in Fayoum province and their potential hazards, a total of 64 random samples of Bivalve Mollusks (Callista Florida species) were collected from the fish markets of Fayoum City, (Wadi Elrayan), Egypt The results revealed that the mean residues of Hg, Pb, Cd, As and Cr were 0.75, 0.77, 0.089, 7.285 and 0.011 mg/kg/ww, respectively. All samples examined for Hg and As exceeded the PML while Pb and Cd lied with the PML The collected samples were subjected to soaking in running water for 30 minutes; soaking in 5% acetic acid solution for 30 minutes and boiling with 5% acetic acid solution for 15 minutes .The heights reduction % of heavy metals residual levels were recorded after treatment in boiling 5% acetic acid treatment with the following reduction %; Hg (80%), Pb (67.6%), Cd (77.5%), As (44.35%) and Cr (75.76%). The assessment of Hazard quotient (HQ) and hazard index (HI) value was exceeded 1 which indicates a potential risk to human health and TR was > 1x10-4 which indicates a carcinogenic risk to the local consumers and will face high chronic risk if they consume Bivalve Mollusks on regular basis in their diet.